Evaluating the websites of small-and-medium-sized hotels (SMHs) in Malaysia - Ayob, Mohd Faizal; Manaf, Za (2015)
This study develops a set of evaluation criteria to evaluate the websites of small-and-medium-sized hotels (SMHs) in Malaysia and to identify current levels of sell-side e-commerce among SMHs in Malaysia. Each of the criteria is evaluated by a 5-point Likert scale rating.The study scaned thoroughly 33 websites of the SMHs located in Kuala Lumpur. The preliminary findings suggest that 51.5 percent of the websites are easy to access, but have no site map or search engine provided within the website.90.9 percent of the websites do not offer a customer loyalty program.A total of 75.8 percent of SMHs do not provide a privacy and security policy on the website.This study concludes that the current levels of sell-side e-commerce among SMHs in Kuala Lumpur, Malaysia is at level 4, which is an interactive site supporting transactions with users.This research has implications for hotel practitioners, specifically to SMHs in the context of website development as they move to higher levels of sell-side e commerce.